2007
DOI: 10.1681/asn.2006101165
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Chronic Kidney Disease and Cognitive Function in Adults 20 to 59 Years of Age

Abstract: Previous studies among elderly suggest an association between chronic kidney disease (CKD) and cognitive impairment. The purpose of this study was to determine whether moderate CKD is associated with cognitive performance among young, healthy, ethnically diverse adults. Three computerized cognitive function tests of visual-motor reaction time (Simple Reaction Time), visual attention (Symbol Digit Substitution), and learning/concentration (Serial Digit Learning) were administered to a random sample of participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
4
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 32 publications
4
123
4
6
Order By: Relevance
“…However, this finding is in contrast to most other previous cross-sectional studies (10,11,(42)(43)(44). Our results may differ from these studies because of various population characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this finding is in contrast to most other previous cross-sectional studies (10,11,(42)(43)(44). Our results may differ from these studies because of various population characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings emphasize that dynamic characteristics of albuminuria are important determinants of cognitive decline. Several studies have shown that moderate CKD can be associated with impaired cognition (38)(39)(40)(41). There are few studies, however, that have longitudinally examined the effect of eGFR decline on cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Declarative memory also depends on signals from the hippocampus and other parts of the medial temporal lobe of the brain for its retention. Neuropsychological studies have found loss of memory and defects in cognition as silent features of renal failure in patients (Hailpern et al 2007). Another explanation for the association of the kidney with cognitive dysfunction is the accumulation of retention solutes.…”
Section: Memory Retention and Cognitionmentioning
confidence: 99%